Processo de reestruturação da saúde pública no estado do Maranhão: um estudo a partir do Programa Saúde é Vida - MACIEL, Sergiane Maia (2018)
This is an evaluative research that sought to apprehend the process of implementation of the Health and Life Program. To this end, the socioeconomic and political-institutional context of Maranhão has been recomposed since the program was created. Three municipalities in Maranhão participated: Morros, Coroatá and Lago dos Rodrigues; selected in terms of the Human Development Index (HDI) and hospital size, considering two dimensions: expansion of the care network in the medium and high complexity and improvement of the qualified assistance of the health services. We used the quantitative and qualitative approach, the use of documentary sources, official statistical bases, observations, records of the hospitals surveyed, semi-structured interviews and news reports by the media about the object of study. A total of 91 subjects were interviewed, being 03 hospital managers, 31 health professionals and 57 users, from January to September 2017. The theoretical categories analyzed were State, Public Policies, Health Systems and Hospital. State was understood in the Marxist perspective, that is, as part of a broader social system whose purpose is to favor the process of capital accumulation. Social policies, such as health policies, were discussed as an expression of the social struggle of workers, which, in the present time, turn to the acquisition of new rights or maintenance of those historically conquered that conform the systems of social protection. The health systems that aggregate the public policies were seen because they attend in an organized way the demands and the social rights. Hospitals were considered because they are an expression of the health system, in which there is a contradiction between the SUS format and its practice oriented by fragmented services, attuned to the hospital-centered model. The "Health and Life Program" is considered to have contributed to medium and high complexity care by allowing access to certain health services. However, it is understood that the restructuring of health services must go further. On the one hand, besides access, it is necessary, according to SUS regulations, to have comprehensive assistance, in view of which the access criterion needs to be dialectically combined with a rational resource management that articulates economies of scale and quality of care services at all levels, starting with basic care.